DIGITAL EDUCATIONAL RESOURCES FOR THE DEVELOPMENT OF MEDIA LITERACY: UKRAINIAN AND INTERNATIONAL EXPERIENCE - Kolisnichenko, Angelina; Kapeliushna , Tetiana (The Modern Higher Education Review, 2025)
The article examines contemporary digital educational resources that contribute to the development of media literacy in Ukrainian and international contexts. Rapid technological progress, the spread of misinformation, and the emergence of synthetic media have intensified the need for effective media-literacy education. The study analyses a wide range of digital tools, including online courses, interactive platforms, methodological guides, and professional development programs, and evaluates their potential to strengthen critical thinking, information verification skills, and digital safety. Through content analysis and comparative review, the research highlights the pedagogical value, structural features, and thematic focus of key resources, including national media-literacy initiatives, international MOOCs, fact-checking guides, and professional educator programmes. The findings demonstrate that digital resources offer accessible, scalable, and practice-oriented opportunities for enhancing information resilience among diverse learner groups. Both Ukrainian and global experiences underscore the importance of integrating media literacy into formal and non-formal education, as well as adapting instructional strategies to emerging digital threats, including deepfakes and algorithmically curated content. The study concludes that continuous innovation, cross-sector collaboration, and systematic support are essential for building an informed and resilient society capable of resisting manipulation in the digital information environment.